STRATEGI PENGEMBANGAN GEOPRODUK LAUT DALAM UPAYA PERTUMBUHAN EKONOMI LOKAL DESA JEPITU, GIRISUBO-GUNUNGKIDUL - Mulyaningsih, Sri -; Mulyaningsih, Sri Mulyaningsih; Rahmawati, Nur; Vienastra, Septian; Suhartono, Suhartono; Wahyu Jati, Michael Fatah Wahyu Jati; Istiqomah, Nurul Istiqomah; Emiliana, Maria Emiliana; Hidayati, Fika Hidayati; Wardana, M. Arif Wardana (Jurnal Abdi Masyarakat Indonesia (JAMIN), 2025)
Socio-political uncertainty, sluggish economic growth, and the looming threat of a potential "Megathrust" along the southern coast of Java have significantly impacted tourism flow, as observed in Yogyakarta, Garut, and Sukabumi. Amid these challenges, the Special Region of Yogyakarta is actively pursuing its Regional Medium-Term Development Plan through 2025, positioning the area as a new center for economic growth. This paper explores the efforts of Jepitu Village to optimize the potential of marine-based geo-products as a strategic response. Community empowerment initiatives, including mentoring, training, and the application of innovative technologies, have been implemented to enhance local capacity and improve the marketing of marine geoproducts. These efforts have increased motivation and enthusiasm among local MSME partners to produce seafood-based products, improved community understanding of digital marketing systems, and taken initial steps toward implementation. The developed products have undergone testing for nutritional content, presentation aesthetics, and cooking methods. Looking forward, it is expected that the local community will be better equipped to anticipate socio-political and economic disruptions, and to engage in self-mitigation efforts in response to the ever-present threat of a "Megathrust" event.